Parametric study of the compaction effect and the response of an oscillation roller. Issue 1 (25th February 2020) - Paulmichl, Ivan; Adam, Christoph; Adam, Dietmar
Abstract : This paper examines the influence of different model and operating parameters of an oscillation roller on the compaction effect and the response behaviour. The main objective is the validation of a recently established continuous compaction control parameter for oscillation rollers. The study is based on a numerical model of the dynamic roller–soil interacting system, in which the intergranular strain enhanced hypoplastic constitutive model is implemented to predict the achieved soil compaction more realistically. The computed drum acceleration is compared with data recorded in field tests. One result is that the roller speed has a significant effect on the soil compaction achieved. The outcomes of this study confirm that the quantities derived from the drum response are basically suitable as indicators for continuous compaction control with oscillation rollers.